KIAI DAN POLITIK; RELASI ULAMA DAN UMARA DALAM MEWUJUDKAN PERDAMAIAN UMAT BERAGAMA DAN BERNEGARA - Ridho, Hilmi; Abdul Wasik; Sobri Washil (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2021)
Post-reform, the involvement of kiai in politics is practically not a new phenomenon. However, it invites pros and cons in the midst of society. The group that agrees is very supportive of the rise of kiai in the political arena, considering that the kiai's role is very strategic in development and peace towards a better, just and prosperous country and become a community figure in their actions. While those who do not agree, argue that politics is something that is unclean so that it is inappropriate for a kiai to be a figure who is considered holy. This paper is studied in order to reveal what is actually behind the purpose of engaging the kiai in practical politics and how a kiai can improve his image in the negative view of society. Politics should be intended to serve the people. The existing power must be used as a tool to fight for the main mission, namely the welfare of the community. A kiai must also be clear that their involvement is an effort to respond to changes that refer to a social structure that is more just, democratic, and able to answer the most basic needs of the people.